Energy Taxes and Natural Gas Demand in EU-Countries - Frank Asche; Petter Osmundsen; Ragnar Tveterås (Center for Economic Studies and ifo Institute (CESifo), 2001)
Producers or consumers faced with an increase in taxes are usually able to shift parts of it to other levels in the value chain. We examine who is actually bearing the burden of increased energy taxes in the EU-area - consumers or exporters. Traditional tax incidence theory presumes spot markets. Natural gas in the EU-area, however, is to a large extent regulated by incomplete long-term contracts. Still, spot market forces could be indicative for tax shifting, by determining the ex post bargaining power in contract renegotiations. By examining tax shifting in actual gas sales contracts we test whether this is the case. To calculate tax incidence we derive demand elasticities, income elasticities and cross price elasticities for natural gas, oil and electricity, for different market segments (households, industry, power generators) in EU countries. Particular focus is on tax incidence in gas markets regulated by incomplete long-term contracts. Based on our findings we discuss normative energy tax issues related to revenue, environmental obligations and security of supply.
Keywords: D63; G18; H23; K12; L72; Q48; 330; Energy Markets; incomplete contracts; tax incidence